Effect of different Mesona chinensis polysaccharides on pasting, gelation, structural properties and in vitro digestibility of tapioca starch-Mesona chinensis polysaccharides gels. (February 2020) - Xiao, Yuehuan; Liu, Suchen; Shen, Mingyue; Jiang, Lian; Ren, Yanming; Luo, Yu; Xie, Jianhua
Abstract: The effects of Mesona chinensis polysaccharides (MCP) obtained through cellulase-assisted (MCP-C) and sodium carbonate-assisted (MCP-S) extractions on the pasting, gelation, structural properties, and in vitro digestibility of tapioca starch (TS)-MCP gels were investigated. The pasting, rheological, gelation and structural properties of TS/MCPs were analyzed by rapid visco analysis (RVA), rheological analysis, texture analysis, X-ray diffraction, fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), respectively. And the digestibility extent of TS/MCPs was determined by an in vitro method. The expansion degree of starch granules, pasting viscosity, hardness, and the amount of amylose leached of TS were decreased after adding MCP-C and increased after adding MCP-S. TS/MCPs showed higher storage modulus ( G′ ), higher short-range order and finer structure than that of TS. In addition, MCP-C and MCP-S decreased the content of rapidly digestible starch (RDS) of TS, especially when 0.5% MCP-C was added. Moreover, the slowly digestible starch (SDS) and resistant starch (RS) contents of TS/MCPs were positively correlated with the G′ and DO, thereby indicating that the strong and ordered gel network had a retardant impact on starch digestion. Graphical abstract: Image 1 Highlights: The hardness and pasting viscosity of TS/MCP-C and TS/MCP-S were completely opposite. The MCP-S treated gels have higher ordered structure and thicker cell walls. MCP-C and MCP-S can mitigate the hydrolysis of TS. The G′, DO and DD values of TS/MCPs were positively correlated with the RS contents.